Understanding computers today and tomorrow - Morley, Deborah; Parker, Charles S. 1945- (Thomson/Course Technology, 2004)
This is a comprehensive approach to Basic through intermediate computer concepts. Known for its readability and the depth of topics covered, this book also includes an interactive website, which contains web tutors, further explorations, and links to new TechTV video projects.